LncRNA MTX2-6 Suppresses Cell Proliferation by Acting as ceRNA of miR-574-5p to Accumulate SMAD4 in Esophageal Squamous Cell Carcinoma - Li, Jie; Han, Xu; Gu, Yan; Wu, Jixiang; Song, Jianxiang; Shi, Zhan; Chang, Huiwen; Liu, Ming; Zhang, Yajun (Frontiers in Cell and Developmental Biology, 2021)
Esophageal squamous cell carcinoma (ESCC) has been one of the key causes of cancer deaths worldwide. It has been found that long non-coding RNA (lncRNA) is related to the generation and progression of various cancers (including ESCC). However, there are still many lncRNAs related to ESCC whose functions and molecular mechanisms have not been clearly elucidated. In this study, we first reported that lncRNA MTX2-6 was significantly downregulated in ESCC tissues and cell lines. The decreased expression of MTX2-6 is closely related to larger tumor and worse prognosis of ESCC patients. Through a series of functional experiments, we detected that overexpressed MTX2-6 inhibited cell proliferation and promoted cell apoptosis of ESCC in vitro and in vivo. Further studies showed that MTX2-6 exerts as a competing endogenous RNA (ceRNA) by binding miR-574-5p and elevates the expression of SMAD4 in ESCC. In summary, our results clarify the tumor suppressor roles of MTX2-6/miR-574-5p/SMAD4 axis in the progression of ESCC and provide emerging therapeutic targets for ESCC patients.